Taller de clowns para mejorar la autorregulación de emociones en los estudiantes de 3 años en la I.E. 1591 Trujillo, 2018. - Venegas Ganoza, Karem Giovanna (2019)
The purpose of this research is to determine whether the clowns workshop influenced the self-regulation of emotions in 3-year-old children from the Preschool 1591 “La Casa del Niño”._x000D_ To carry out this research, 21 children in the classroom were selected, including boys and girls, to whom the class sessions was applied._x000D_ In the pre-test the children reached a medium level, which means that they are in the middle of a process of self-regulation of emotions. This result would also mean that the teacher was not using strategies for children to develop this emotional aspect better._x000D_ After having applied the programmed sessions, we carried out the post-test, which gave us a better result than the one obtained before. Showing that the children significantly increased in their emotional self-regulation